A silane coupling agent and its application in photovoltaic adhesive film

By introducing a silane coupling agent with a high conjugated large Π bond structure and alkoxy silane group into the photovoltaic adhesive film, the problem of ultraviolet aging resistance and insufficient glass adhesion of the photovoltaic adhesive film is solved, and the problem of ultraviolet aging resistance and insufficient glass adhesion of the photovoltaic adhesive film is significantly improved. Durability and bonding strength extend the service life of solar panels.

CN118561904BActive Publication Date: 2024-12-27SUZHOU YISHENG OPTICAL MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411035371.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-27
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The existing photovoltaic adhesive films have shortcomings in ultraviolet aging and glass adhesion, resulting in a decrease in the photoelectric conversion efficiency of solar panels.

Method used

A silane coupling agent is adopted, which absorbs ultraviolet energy through a highly conjugated large Π bond structure and forms a chemical bond between the adhesive film and glass through alkoxy silane groups to improve the resistance to UV aging of the adhesive film. Performance and bonding strength.

Benefits of technology

It significantly improves the UV aging resistance of the photovoltaic adhesive film and the bonding strength to the glass, extends the service life of the adhesive film and maintains high light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The present invention relates to a silane coupling agent and its application in a photovoltaic adhesive film. The silane coupling agent has a novel structure, can be prepared by a simple coupling reaction, has readily available raw materials, and is simple to operate. In addition, the introduction of the silane coupling agent of the present invention into the photovoltaic adhesive film can effectively improve the UV aging resistance of the adhesive film and the bonding strength with glass. On the one hand, the silane coupling agent has a highly conjugated large π bond structure, which can effectively absorb the energy of ultraviolet rays, so that the adhesive film has good UV aging resistance; on the other hand, a plurality of alkoxysilane groups are introduced into the silane coupling agent, which can form a strong chemical bond between the adhesive film and the glass, thereby increasing the adhesion between the adhesive film and the glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic chemistry, and specifically relates to a silane coupling agent and application thereof in photovoltaic adhesive films. Background Art

[0002] Photovoltaic film is a kind of film material applied to solar panels. It is usually a transparent polymer film used to cover the surface of solar panels. The film mainly has the functions of waterproofing, dustproofing, and increasing the photoelectric conversion rate. It can protect the surface of the panel from damage by sunlight, wind and rain, and pollutants, and improve the light absorption rate and efficiency of the panel. As a key packaging material for solar panels, photovoltaic film is rich in variety. According to the differences in material and performance, it is mainly divided into EVA film, POE film, EPE film, PDMS film, PVB film, PU film, and ion cross-linking film.

[0003] In photovoltaic modules, photovoltaic film is one of the core packaging materials. Photovoltaic film undergoes a high-temperature lamination step and bonds the cell sheet and glass or backplane together through a cross-linking reaction. However, the existing photovoltaic film uses POE resin or EVA resin as the matrix resin. After the film is pre-cross-linked by electron irradiation, the bonding strength between the film and the glass becomes poor, especially after aging, the peel strength between the film and the glass is lower. In addition, photovoltaic film has high requirements for light stabilizers. At present, the light stabilizers that can be used for packaging films on the market are generally benzophenone or benzotriazole ultraviolet absorbers and hindered amine light stabilizers. Benzophenone and benzotriazole ultraviolet absorbers are easy to react with free radicals to form chromophores, and they will also decompose and fail due to the long-term action of heat and oxygen, causing the EVA film to turn yellow, thereby affecting its high light transmittance, and ultimately leading to a decrease in the photoelectric conversion efficiency of solar panels.

[0004] Based on this, improving the UV aging resistance of photovoltaic films and increasing the adhesion between films and glass are issues that need to be addressed urgently. Summary of the invention

[0005] The main purpose of the present invention is to provide a silane coupling agent and its application in photovoltaic adhesive film, which has solved the existing problems of poor UV aging resistance and low adhesion to glass.

[0006] First, the present invention provides a silane coupling agent, which is a compound shown in Formula 1:

[0007]

[0008] Among them, R1-R 12 Each independently selected from C 1-6 Alkyl and C 3-8 Cycloalkyl, the C 1-6Alkyl and C 3-8 The cycloalkyl group may be optionally substituted with 1, 2, 3, 4 or 5 substituents selected from H, D, F, Cl, Br and I.

[0009] In some embodiments, R1-R 12 Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, -CHF2, -CF3, -CHFCH2F, -CF2CHF2, -CH2CF3 and -CH2CF2CHF2.

[0010] In some embodiments, it is a compound having one of the following structures:

[0011] , , .

[0012] Secondly, the present invention also provides a photovoltaic composition, which comprises the above-mentioned silane coupling agent.

[0013] In some embodiments, the photovoltaic composition comprises the following raw materials, by weight:

[0014] 100 parts of base resin, 0.5-1 parts of crosslinking agent, 0.1-0.5 parts of initiator, 1-5 parts of the above-mentioned silane coupling agent, and 1-5 parts of glycidyl methacrylate.

[0015] In some embodiments, the base resin is selected from one or more of POE resin, EVA resin and PVB resin.

[0016] In some embodiments, the crosslinking agent is selected from one or more of ethylene glycol dimethacrylate, butanediol dimethacrylate, hexanediol dimethacrylate, and trimethylolpropane trimethacrylate;

[0017] In some embodiments, the initiator is selected from one or more of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylperoxycarbonate-2-ethylhexyl ester, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and tert-butylperoxyisopropyl carbonate.

[0018] The present invention also provides a photovoltaic adhesive film, the raw material of which is the photovoltaic composition.

[0019] In addition, the present invention also provides a method for preparing the above photovoltaic adhesive film, the preparation method comprising:

[0020] Step 1: Weigh the raw materials according to the ratio and stir evenly;

[0021] Step 2: Add the mixture stirred evenly in step 1 into an extruder for mixing and plasticizing, melt extrusion, cast film, and winding to obtain a photovoltaic film.

[0022] Finally, the present invention also requests protection for the application of the above-mentioned photovoltaic film in a photovoltaic module, wherein the photovoltaic module comprises a first glass, a first film, a battery cell, a second film, a second glass or a back panel stacked in sequence, and the first film and the second film are each independently a photovoltaic film prepared by the above-mentioned method.

[0023] The present invention has the following beneficial effects:

[0024] 1) The silane coupling agent prepared by the present invention has a novel structure, can be prepared by a simple coupling reaction, has readily available raw materials, and is simple to operate.

[0025] 2) Introducing the silane coupling agent of the present invention into the photovoltaic adhesive film can effectively improve the film's UV aging resistance and the bonding strength with glass. On the one hand, the silane coupling agent has a highly conjugated large π bond structure, which can effectively absorb the energy of ultraviolet rays, so that the film has good UV aging resistance; on the other hand, the silane coupling agent introduces multiple alkoxysilane groups, which can form a strong chemical bond between the film and the glass, thereby increasing the adhesion between the film and the glass. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention is further explained below in conjunction with specific implementation modes.

[0028] Example 1: Preparation of 1,1,2,2-tetrakis(4-(2-(trimethoxysilyl)ethyl)phenyl)ethylene (Compound 1)

[0029]

[0030] Under nitrogen environment, compound I (83.6 g, 0.1 mol), compound II (137.4 g, 0.6 mol), Na2CO3 (106 g, 1.0 mol), Pd(PPh3)4 (0.02 mol) were added to the reactor, and then deoxygenated toluene (500 mL) and water (100 mL) were added, and the temperature was raised to 110 ° C and stirred for 10 hours. After the reaction, the filtrate was filtered, and the filtrate was washed with deionized water 3 times (200 mLx3), the organic layer was dried over anhydrous sodium sulfate, and concentrated under reduced pressure to obtain a crude product, which was separated and purified by column chromatography to obtain compound 1 as a white solid with a yield of 59.3% and an HPLC purity of 99.1%.

[0031] LC-MS (ESI): [M+H] + =925.4.

[0032] 1 H-NMR (500 MHz, CDCl3): δ(ppm): 7.48-7.35(m,8H), 6.75-6.69 (m,8H), 3.51-3.43 (m,36H), 2.43-2.36 (m,8H), 0.95-0.87 (m,8H).

[0033] Example 2: Preparation of 1,1,2,2-tetrakis(4-(2-(triethoxysilyl)ethyl)phenyl)ethylene (Compound 2)

[0034]

[0035] Under nitrogen environment, compound I (83.6 g, 0.1 mol), compound II (135.5 g, 0.5 mol), Na2CO3 (84.8 g, 0.8 mol), Pd(PPh3)4 (0.01 mol) were added to the reactor, and then deoxygenated toluene (500 mL) and water (100 mL) were added, and the temperature was raised to 100 ° C and stirred for 13 hours. After the reaction, the filtrate was filtered, and the filtrate was washed with deionized water 3 times (200 mL x 3). The organic layer was dried over anhydrous sodium sulfate and concentrated under reduced pressure to obtain a crude product. The crude product was separated and purified by column chromatography to obtain compound 2 as a white solid with a yield of 53.5% and an HPLC purity of 99.3%.

[0036] 1 H-NMR (500 MHz, CDCl3): δ(ppm): 7.46-7.37(m,8H), 6.77-6.70 (m,8H), 3.80-3.72 (m,24H), 2.51-2.44 (m,8H), 1.25-1.16 (m,36H), 0.92-0.86 (m,8H).

[0037] Example 3: Preparation of 1,1,2,2-tetrakis(4-(2-(isopropoxysilyl)ethyl)phenyl)ethylene (Compound 3)

[0038]

[0039] Under nitrogen environment, compound I (83.6 g, 0.1 mol), compound II (187.8 g, 0.6 mol), Na2CO3 (106 g, 1.0 mol), Pd(PPh3)4 (0.02 mol) were added to the reactor, and then deoxygenated toluene (500 mL) and deionized water (100 mL) were added, and the temperature was raised to 110 ° C and stirred for 10 hours. After the reaction, the filtrate was filtered, and the filtrate was washed with deionized water 3 times (200 mL x 3). The organic layer was dried over anhydrous sodium sulfate and concentrated under reduced pressure to obtain a crude product. The crude product was separated and purified by column chromatography to obtain compound 3 as a white solid with a yield of 50.8% and an HPLC purity of 99.3%.

[0040] 1 H-NMR (500 MHz, CDCl3): δ(ppm): 7.50-7.45(m,8H), 6.83-6.72 (m,8H), 3.87-3.81 (m,12H), 2.64-2.59 (m,8H), 1.28-1.24 (m,72H), 0.91-0.84 (m,8H).

[0041] Application test examples

[0042] 1. Preparation of photovoltaic film

[0043] Test Example 1

[0044] Step 1: Weigh 100 parts of EVA resin (VA content 28%, melt index 40 g / 10min, purchased from DuPont, USA), 0.5 parts of ethylene glycol dimethacrylate, 0.5 parts of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, 5 parts of the silane coupling agent (Compound 1) prepared in Example 1, and 5 parts of glycidyl methacrylate according to mass ratio, and stir to mix;

[0045] Step 2: Add the mixture mixed evenly in step 1 to an extruder for mixing and plasticizing, melt extrusion, casting into a film, and winding to obtain a photovoltaic film.

[0046] Test Example 2

[0047] Step 1: Weigh 100 parts of EVA resin (VA content 28%, melt index 40 g / 10min, purchased from DuPont, USA), 1 part of butanediol dimethacrylate, 0.3 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 5 parts of the silane coupling agent (Compound 2) prepared in Example 2, and 5 parts of glycidyl methacrylate according to the mass ratio, and stir and mix;

[0048] Step 2: Add the mixture mixed evenly in step 1 to an extruder for mixing and plasticizing, melt extrusion, casting into a film, and winding to obtain a photovoltaic film.

[0049] Test Example 3

[0050] Step 1: Weigh 100 parts of EVA resin (VA content 28%, melt index 40 g / 10min, purchased from DuPont, USA), 0.8 parts of hexanediol dimethacrylate, 0.5 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 5 parts of the silane coupling agent (Compound 3) prepared in Example 3, and 5 parts of glycidyl methacrylate according to the mass ratio, and stir to mix;

[0051] Step 2: Add the mixture mixed evenly in step 1 to an extruder for mixing and plasticizing, melt extrusion, casting into a film, and winding to obtain a photovoltaic film.

[0052] Comparative Example 1

[0053] The silane coupling agent described in Example 1 is replaced by a silane coupling agent commonly used in the art. Vinyl trimethoxysilane alkyl , the specific operations are as follows:

[0054] Step 1: Weigh 100 parts of EVA resin (VA content 28%, melt index 40 g / 10min, purchased from DuPont, USA), 0.5 parts of ethylene glycol dimethacrylate, 0.5 parts of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, 5 parts of vinyl trimethoxysilane, and 5 parts of glycidyl methacrylate according to the mass ratio, and stir to mix;

[0055] Step 2: Add the mixture mixed evenly in step 1 to an extruder for mixing and plasticizing, melt extrusion, casting into a film, and winding to obtain a photovoltaic film.

[0056] 2. Performance Testing

[0057] The photovoltaic adhesive films provided in the above-mentioned test examples 1-3 and comparative example 1 were sampled according to the method specified in the performance test standard, and their resistance to ultraviolet aging and peeling strength with glass were tested.

[0058] 1) UV aging resistance: The obtained photovoltaic film was subjected to UV irradiation aging test according to the requirements of IEC61345 standard. Test conditions: the thickness of the photovoltaic film is 0.5mm, the size is 30mm x 10mm, the surface temperature of the test piece is 60±5℃, the UV wavelength range is 280-400nm, the irradiation intensity is 15kW·h / m, and the UV irradiation test time is 2000h.

[0059] The visible light transmittance before and after the test was measured, and the visible light transmittance retention rate was calculated according to the following formula:

[0060] Retention rate of visible light transmittance=average light transmittance after the test / average light transmittance before the test×100%.

[0061] The yellowing index (△YI) before and after the test was measured according to GB 2409.

[0062] 2) Peel strength:

[0063] Sample preparation: 1) Prepare two pieces of photovoltaic film (thickness 0.5mm), one piece of glass and one piece of flexible backplane with the size of 300mm×150mm respectively; 2) Stack the glass / photovoltaic film (two pieces) / flexible backplane in sequence, put them into a vacuum laminator, and laminate them at 120℃ for 15min. There should be no bubbles in the film of the sample after lamination. Prepare 3 samples; 3) Cut the flexible backplane / photovoltaic film layer into samples with a width of 10mm±0.5mm every 5mm in the width direction for the peeling force test between the photovoltaic film and the glass.

[0064] Test process: According to the test method of GB / T2790-1995, the peeling force F between the glass and the film is measured on a tensile testing machine at a tensile speed of 100mm / min±10mm / min.

[0065] Test results: The peel strength is calculated according to the following formula, and the arithmetic mean of 3 samples is taken, accurate to 0.1N / cm.

[0066] σ=F / B

[0067] Where: σ—180° peel strength, N / cm; F—peel force, N; B—sample width, cm.

[0068] The specific steps of the aging treatment are: placing the sample in an aging box with a temperature of 120° C. and a humidity of 100%, and taking it out for testing after 24 hours and 48 hours respectively.

[0069] The above performance test results are shown in Table 1.

[0070] Table 1 Photovoltaic film performance test

[0071]

[0072] As can be seen from Table 1, the photovoltaic adhesive film prepared by the present invention has excellent UV aging resistance and bonding performance. The main reason is that the photovoltaic adhesive film composition of the present invention introduces a silane coupling agent. On the one hand, the silane coupling agent has a highly conjugated large π bond structure, which can effectively absorb the energy of ultraviolet rays, so that the film has good UV aging resistance; on the other hand, multiple alkoxy silane groups are introduced into the silane coupling agent, which can form a strong chemical bond between the film and the glass, increase the adhesion between the film and the glass, and even after 48h aging, the peel strength between the film and the glass does not decrease significantly.

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A silane coupling agent, which is a compound represented by formula 1: , in, R1-R 12 Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, -CHF2, -CF3, -CHFCH2F, -CF2CHF2, -CH2CF3 and -CH2CF2CHF2.

2. The silane coupling agent according to claim 1, which is a compound having one of the following structures: 、 、 。 3. A photovoltaic composition, characterized in that: The photovoltaic composition comprises the silane coupling agent according to any one of claims 1 to 2.

4. The photovoltaic composition according to claim 3, characterized in that The following raw materials are included by weight: 100 parts of base resin, 0.5-1 parts of cross-linking agent, 0.1-0.5 parts of initiator, 1-5 parts of silane coupling agent according to any one of claims 1-2, and 1-5 parts of glycidyl methacrylate.

5. The photovoltaic composition according to claim 4, characterized in that: The matrix resin is selected from one or more of POE resin, EVA resin and PVB resin.

6. The photovoltaic composition according to claim 4, characterized in that: The cross-linking agent is selected from one or more of ethylene glycol dimethacrylate, butanediol dimethacrylate, hexanediol dimethacrylate and trimethylolpropane trimethacrylate; The initiator is selected from one or more of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylperoxycarbonate-2-ethylhexyl ester, and tert-butylperoxycarbonate isopropyl ester.

7. A photovoltaic adhesive film, characterized in that: The raw material of the photovoltaic adhesive film is the photovoltaic composition described in any one of claims 3-6.

8. A method for preparing the photovoltaic adhesive film according to claim 7, characterized in that: The preparation method comprises: Step 1: Weigh the raw materials according to the ratio and stir evenly; Step 2: Add the mixture stirred evenly in step 1 into an extruder for mixing and plasticizing, melt extrusion, cast film, and winding to obtain a photovoltaic film.

9. Use of the photovoltaic adhesive film according to claim 7 in a photovoltaic module, wherein the photovoltaic module comprises a first glass, a first adhesive film, a battery cell, a second adhesive film, a second glass or a back plate stacked in sequence, characterized in that: The first adhesive film and the second adhesive film are each independently the photovoltaic adhesive film as described in claim 7.